Retraction Notice - Rahman, Md. Mujibur (Journal of Medicine, 2018)
On 10th August 2018 the Editorial Board of Journal of Medicine agreed to retract the article ‘Role of CD 20 in Physiopathology of Hodgkin’s Disease’ published in Journal of Medicine, Vol.19(2) pages 119-122 (DOI: <a href="http://dx.doi.org/10.3329/jom.v19i2.37232" target="_blank" data-saferedirecturl="https://www.google.com/url?hl=en-GB&q=http://dx.doi.org/10.3329/jom.v19i2.37232&source=gmail&ust=1534230306617000&usg=AFQjCNFPT2XVtC-4ft3zfEPrsiqz0ziEqA">http://dx.doi.org/10.3329/jom.v19i2.37232 ) as it was found to be a duplicate publication of the following published article: ‘CD20 role in pathophysiology of Hodgkin’s disease’ by Marcelo Antônio Oliveira Santos and Marinus de Moraes Lima published in Revista da Associação Médica Brasileira, Vol.63(9) pages 810-813 http://dx.doi.org/10.1590/1806-9282.63.09.810.